Associations between low food security and subjective memory complaints among Latino adults - Joseph Saenz; Laura Tanner (BMC Public Health)
Abstract Background Low food security is related with worse cognitive outcomes and poor mental health (e.g., higher anxiety and depression) may explain these associations. Subjective memory complaints may be important indicators of everyday memory problems. Despite a higher prevalence of food insecurity among Latinos, few have explored the links between low food security and subjective memory complaints in Latinos, or potential mechanisms underlying the associations. Methods We used the Sangre Por Salud Biobank sample of 2,481 self-reported Latino patients aged 18–85 from a federally qualified community health center in Phoenix, AZ. Food security was assessed using the 6-item Household Food Security Survey Module and subjective memory complaints were measured using the Frequency of Forgetting Scale. We used linear regressions to test associations between low food security and subjective memory complaints, whether associations were explained by anxiety and depression, and whether associations differed by age or biological sex. Results Around 76% of the sample were food secure, with 18% and 6% experiencing low and very low food security, respectively. In multivariate analyses, compared to the food secure, both low and very low food security related with higher subjective memory complaints and these associations were not modified by age or biological sex. Associations between low food security and subjective memory complaints were no longer significant after adjusting for anxiety and depression, suggesting that poor mental health may mediate associations between low food security and subjective memory complaints. Conclusions Experiences of low food security were related with more frequent memory complaints. Subjective memory complaints are related with future cognitive impairment and dementia, making them important early markers of cognitive problems. Future studies should evaluate potential cognitive benefits of addressing food insecurity and its downstream effects on mental health.